Dante and Medieval Virgilianism - Ruiz de Vergara Olmos, Ekaitz (2022)
The conceptualization of the relationship between Virgil and Dante has been one of the most investigated topics in classical tradition and comparative literature studies. The view that has prevailed since the nineteenth century is that of Domenico Comparetti, the coiner of the concept of “classical tradition”, who claimed that Dante had “purified” the popular and legendary image of Virgil. But throughout the twentieth century, other critical perspectives have also been practiced that differ from the scheme proposed by Comparetti. In this article, we analyze medieval Virgilianism: the aesthetic, philosophical, and theological trends that presented certain images of Virgil in the Middle Ages. Dante's Commedia can be explained as a synthesis of the main trends of medieval Virgilianism. Dante considers Virgil a mentor, but in a certain way, he also considers him a heathen author to whom he submits a critical judgment. The conclusion is that Dante is capable of unifying the prophetic vision of Virgil in his poem, held by ecclesiastical authors with the legendary vision of the popular tradition that represented the Mantuan poet as a kind of magician or soothsayer.